Small-Molecule Acetylation Controls the Degradation of Benzoate and Photosynthesis in Rhodopseudomonas palustris - Chelsey M. VanDrisse (American Society for Microbiology, 2018)
ABSTRACT The degradation of lignin-derived aromatic compounds such as benzoate has been extensively studied in Rhodopseudomonas palustris, and the chemistry underpinning the conversion of benzoate to acetyl coenzyme A (acetyl-CoA) is well understood. Here we characterize the last unknown gene, badL, of the bad (benzoic acid degradation) cluster. BadL function is required for growth under photoheterotrophic conditions with benzoate as the organic carbon source (i.e., light plus anoxia). On the basis of bioinformatics and in vivo and in vitro data, we show that BadL, a Gcn5-related N- acetyltransferase (GNAT) (PF00583), acetylates aminobenzoates to yield acetamidobenzoates. The latter relieved repression of the badDEFGAB operon by binding to BadM, triggering the synthesis of enzymes that activate and dearomatize the benzene ring. We also show that acetamidobenzoates are required for the expression of genes encoding the photosynthetic reaction center light-harvesting complexes through a BadM-independent mechanism. The effect of acetamidobenzoates on pigment synthesis is new and different than their effect on the catabolism of benzoate. IMPORTANCE This work shows that the BadL protein of Rhodopseudomonas palustris has N-acetyltransferase activity and that this activity is required for the catabolism of benzoate under photosynthetic conditions in this bacterium. R. palustris occupies lignin-rich habitats, making its benzoate-degrading capability critical for the recycling of this important, energy-rich biopolymer. This work identifies the product of the BadL enzyme as acetamidobenzoates, which were needed to derepress genes encoding benzoate-degrading enzymes and proteins of the photosynthetic apparatus responsible for the generation of the proton motive force under anoxia in the presence of light. In short, acetamidobenzoates potentially coordinate the use of benzoate as a source of reducing power and carbon with the generation of a light-driven proton motive force that fuels ATP synthesis, motility, transport, and many other processes in the metabolically versatile bacterium R. palustris.